ANALISIS PERAN LITERASI DIGITAL DALAM MENINGKATKAN INTENSI BERWIRAUSAHA DIGITAL: SEBUAH KAJIAN LITERATUR - Faikha, Roudotul; Nurlaili, Eka Indah (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
This study aims to explain the findings of research that analyzes how digital literacy affects the intention to become a digital entrepreneur. This study is a qualitative study using the Systematic Literature Review (SLR) method. Several articles with a period of five years (2015 - 2024) that have been collected from Google Scholar, Research Gate, Scopus, Emerald, and other supporting sources are selected using the PRISMA SLR method and grouped according to the focus of the theme. The results of the study indicate that digital literacy has an important role and positive impact in increasing entrepreneurial intentions because it can provide an understanding of the basics of starting a business and inspire or develop entrepreneurial ideas, which will make the younger generation more creative and innovative.